Engaging with modernity: need for a critical negotiation - Kumar, D.V. (2008)
Modernity has emerged as a dominant category in social science literature. An attempt is made in this paper to make sense of what modernity is and elaborate and interrogate different forms of engagement one could pursue with it. One could approach modernity in three different, though not contradictory, ways. Similarly, it is possible to think of three distinct forms of engagement which one can pursue with modernity. the case for one form of engagement, namely, critical and creative negotiation, is argued. - Reproduced.
Keywords: Modernism